Medıa Propaganda Agaınst Indıa’s Muslım Communıty In The Post-Covıd-19 - Rifqi Fahmi; Ali Maksum; Reevany Bustami (Cita Konsultindo Research Center, 2024)
Indian mass media propaganda on issues regarding Muslim minorities has led to non-verbal discriminatory actions. This is proven by the accusations experienced by Muslim groups which are disseminated through various platforms, both local media and social media. This propaganda certainly had a big influence on India's Hindu majority community, which had previously been at odds with the Muslim minority group in India since the time of the Delhi Sultanate. Since being led by a party that is not happy with the development of Islam, the Indian government has become a country that tends to be undemocratic. The Muslim minority really regrets this and says that Islamophobia is very much felt in India today. This kind of phenomenon certainly cannot be separated from the propaganda of local media which is directly controlled by the government as well as several other media such as Facebook, WhatsApp and others. This qualitative research will explain the impact of media propaganda and the bad sentiments that arise due to propaganda against Muslim minority groups in India. The government often uses the media as a political instrument to shape and even stigmatize minority groups. Furthermore, these broadcasts have influenced Indian netizens to continue pushing propaganda by creating racist and insensitive memes against the Muslim community. This situation shows an Islamophobic environment, as both mainstream news media and social media discriminate against the Muslim community without any actual facts on the ground. However, behind the propaganda, the role of the Indian government has not been proven to be able to minimize the problem, ironically exacerbating cases of Islamophobia in India.